Family Ownership Concentration and Debt in Dividends Policies - Herlina Yoka Roida; Resty Fauzyah Yahya; Nekhasius Agus Sunarjanto (Universitas Prasetiya Mulya, 2022)
This study aims to examine whether or not family control benefiting the internal and external governance mechanism to mitigate to agency problems affecting dividends in a capital market environment to improve investor protection such as Indonesia. The quantitative analysis model was used to test the hypotheses based on the panel data analysis of 58 family firms listed from 2012 to 2019, and the random effect technique (pooled EGLS). The findings indicate that internal governance mechanism (family ownership and family board representation) are irrelevant to the dividend policy. However, external governance mechanism (debt) negatively affects dividends. This means that debt plays a significant role in influencing dividend policies. In addition, it provides the issue from institutional setting, when legal protection for minority shareholders is improving, the governance role of families become less effective to monitor the firms.